Green Products: Factors Exploring the Green Purchasing Behavior of South Indian Shoppers - Rambabu Lavuri; Gugyh Susandy (Indonesian Journal of Sustainability Accounting and Management, 2020)
On the basis of the theory of planned behavior (TPB) approach, this exploratory study aims to examine factors exploring the green purchasing behavior of south Indian shoppers. The research study seeks to expand the planned behavior to include three additional variables, namely, environmental concern, knowledge, and media exposure. Data were collected from 429 respondents from three southern Indian states. Purposive and snowball samplings were adopted in the selection of respondents. The data were analyzed using factor analysis, Pearson's correlation, and multiple regression. The findings concluded that subjective norms have no significant association with the green purchase intention. Variables such as media exposure, environmental concern, environmental knowledge, and perceived behavioral control had a significant impact on the green purchase intention, which, in turn, had a substantial effect on the green purchasing behavior. These results support the TPB model. This research will help green marketers to develop new green strategies and plans to increase sales volumes and build good relationships with targeted green customers.